Using spectrometric analysis for indirect estimation of 146S component concentration while measuring FMDV RNA amount - M. I. Doronin; D. V. Mikhalishin; N. Ye. Kamalova; A. V. Borisov (Ветеринария сегодня)
Foot and mouth disease has a negative impact on economy due to the high cost of eradication campaigns and stringent measures imposed on domestic and international trade in animal products. Prevention and control measures include mass vaccination of susceptible animals and control of post-vaccination immunity level. Concentration of 146S particles, which are the main component affecting the vaccine immunogenicity, is determined during commercial scale production of FMD vaccines. The paper assesses feasibility of spectrometric analysis for indirect determination of 146S component concentration while measuring amount of FMDV RNA isolated after serological binding. This method is cheap, easy-to-use and makes it possible to determine indirectly concentration of FMDV 146S particles in inactivated vaccine raw materials within 3–4 hours. Study of cultural FMDV suspensions shows that the linear model С146S = (3.9 × NRNA 146S + 566,783,689)/ 280,818,944,837 makes it possible to estimate FMDV 146S component concentration in the vaccine raw materials with the help of a spectrometric analysis. The actual results obtained in real-time reverse transcription – polymerase chain reaction (rtRT-PCR) were 97.0–99.9% consistent with the expected results of the spectrometric analysis used to determine cultural FMDV 146S component concentration. When compared to a complement fixation test, the actual results were 94.5–99.5% in line with the expected ones. The actual results for positive control were 99.0–99.6% in line with the expected ones. As expected, no FMDV genome or 146S particles were detected in the negative control sample.